A coumarin-based fluorescent probe for monitoring labile ferrous iron in living systems. Issue 11 (3rd May 2018) - Long, Lingliang; Wang, Ning; Han, Yuanyuan; Huang, Meiyu; Yuan, Xiangqi; Cao, Siyu; Gong, Aihua; Wang, Kun
Abstract : A fluorescent probe for sensing labile Fe 2+ levels has been rationally constructed based on a novel Fe 2+ mediated cyclization reaction. Abstract : Labile Fe 2+ has been considered to be a metabolically active and regulatory form of cellular iron. Monitoring the dynamic level of labile Fe 2+ in biological systems is vital for evaluating the iron related biological processes and diseases as well as dissecting the exact physiological and pathophysiological functions of the labile Fe 2+ . Herein, we rationally constructed a coumarin-based fluorescent probe for sensing labile Fe 2+ in living systems based on a novel Fe 2+ meditated cyclization reaction strategy. The probe showed a highly selective and sensitive response to Fe 2+, and the detection limit was determined to be 45 nM. Significantly, the probe displayed fast response to Fe 2+, with the sensing reaction completed in 2 min, which is beneficial for real time sensing. The application of the probe for sensing different concentrations of labile Fe 2+ in living cells has been conducted. In addition, the basal and endogenous levels of labile Fe 2+ in living systems were also successfully monitored.